Efficiency of HPV DNA Test versus Pap Smear in the Screening of Cervical Cancer - Pradhan, Renee; Pant, U.; Aryal, B. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Cancer cervix is a common genital cancer. Human papillomavirus is the main cause of cervical cancer because of the strong association of certain HPV genotypes and the development of cervical cancer and its precursor lesions, cervical intraepithelial neoplasia CIN 2 or CIN3. Methods: The study was conducted on 180 gynecological patients seen at the outpatient department of Manipal Hospital, Bangalore. A comparative study of HPV DNA test with Pap smear in the screening of cervical neoplasia was carried out over the period of 24 months from August 2011 to June 2013. Results: The incidence of cervical cancer and its associated mortality has declined in recent years, largely due to the widespread implementation of screening programs by Pap smear testing. The management and the prevention of cervical cancer should change with HPV DNA testing for high risk HPV, which is more sensitive than pap smear testing. Infection of cervix with HPV is necessary to cause cervical neoplasia and cervical cancer. Persistent infection with HPV is required for the development of cervical dysplasia and invasive cervical cancer. Conclusions: HPV testing alone for primary screening appears promising in women aged 30 years and older as this group is at greatest risk of developing CIN 3. As compared with Pap testing, HPV testing has greater sensitivity for detection of cervical intraepithelial neoplasia.